Linear water waves : a mathematical approach - Kuznet͡sov, N. G. (Nikolaĭ Germanovich) (Cambridge University Press, 2002)
This book gives a self-contained and up-to-date account of mathematical results in the linear theory of water waves. Linear Water Waves will serve as an ideal reference for those working in fluid mechanics, applied mathematics, and engineering.